Kesenjangan Implementasi Artificial Intelligence dalam Tata Kelola Pendidikan Di Era Society 5.0 - Dwi Rahayu; Mardalena Mardalena; Agus Sugianto (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Abstract: The implementation of AI in educational governance faces a significant gap between policy and practice, particularly at the school management level, which has been largely overlooked. This study was a mixed-methods, sequential, explanatory study that analyzed school management's digital readiness, identified inhibiting and enabling factors, and formulated an adaptive governance transformation model in Merangin Regency. Quantitative data were collected from 210 respondents (principals, vice principals, and administrative heads) through surveys, followed by in-depth interviews and FGDs. Results indicate that school management's digital readiness is very low (mean 2.32/5), with managerial digital competence deficit as the most critical dimension (mean 1.92). Border schools and B/C-accredited schools fall into Quadrant III (Foundation Stage), while schools with internal champions reach Quadrant I (Integration Ready). The Staged Transformation Model (3T Model) was formulated as an adaptive solution. This study concludes that the root cause of AI implementation gaps is not technical but managerial and systemic; thus, interventions must focus on strengthening digital leadership capacity, internal policies, and champion development. Policy implications include the need for a national AI adoption roadmap that considers regional disparities in readiness. Keywords: artificial intelligence; educational governance; school management digital readiness; management transformation; Society 5.0 Abstrak: Implementasi AI dalam tata kelola pendidikan menghadapi kesenjangan signifikan antara kebijakan dan praktik lapangan, khususnya pada level manajemen sekolah yang selama ini terabaikan. Penelitian mixed methods sequential explanatory ini bertujuan menganalisis kesiapan digital manajemen sekolah, mengidentifikasi faktor penghambat dan pendorong, serta merumuskan model transformasi tata kelola adaptif di Kabupaten Merangin. Data kuantitatif dikumpulkan dari 210 responden (kepala sekolah, wakil, kepala TU) melalui survei, dilanjutkan wawancara mendalam dan FGD. Hasil menunjukkan tingkat kesiapan digital manajemen sekolah sangat rendah (mean 2,32/5), dengan defisit kompetensi digital manajerial sebagai dimensi paling kritis (mean 1,92). Sekolah perbatasan dan akreditasi B/C berada pada Kuadran III (Tahap Fondasi), sementara sekolah dengan champion internal mencapai Kuadran I (Siap Terintegrasi). Model Transformasi Bertahap (3T Model) dirumuskan sebagai alternatif solusi adaptif. Simpulan penelitian ini menegaskan bahwa akar masalah implementasi AI bukan pada faktor teknis melainkan manajerial-sistemik, sehingga intervensi harus diarahkan pada penguatan kapasitas kepemimpinan digital, kebijakan internal, dan pengembangan champion. Implikasi kebijakan mencakup perlunya peta jalan nasional adopsi AI yang mempertimbangkan disparitas kesiapan antar wilayah. Kata kunci: artificial intelligence; tata kelola pendidikan; kesiapan digital manajemen sekolah; transformasi manajemen; Society 5.0